2018
DOI: 10.1016/j.isci.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Morphine-Induced Inhibition of TTX-R Sodium Channels in Dorsal Root Ganglia Neurons Is Modulated by Gut-Derived Mediators

Abstract: SUMMARYIn the clinical setting, analgesic tolerance is a primary driver of diminished pain control and opioid dose escalations. Integral to this process are primary afferent sensory neurons, the first-order components of nociceptive sensation. Here, we characterize the factors modulating morphine action and tolerance in mouse small diameter dorsal root ganglia (DRG) neurons. We demonstrate that acute morphine inactivates tetrodotoxin-resistant (TTX-R) Na+ channels in these cells. Chronic exposure resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 58 publications
0
45
0
Order By: Relevance
“…A recent study observed that colon tissue supernatants from mice with chronic morphine exposure induced tolerance and hyperexcitability in naive mouse DRG neurons. 77 Oral vancomycin treatment in this paradigm was sufficient to block tolerance development, but not hyperexcitability. This evidence suggests that tolerance development in vivo involves a peripheral, gut-mediated component in addition to the central mechanisms that have been extensively described.…”
Section: Experimental Paradigmsmentioning
confidence: 87%
See 3 more Smart Citations
“…A recent study observed that colon tissue supernatants from mice with chronic morphine exposure induced tolerance and hyperexcitability in naive mouse DRG neurons. 77 Oral vancomycin treatment in this paradigm was sufficient to block tolerance development, but not hyperexcitability. This evidence suggests that tolerance development in vivo involves a peripheral, gut-mediated component in addition to the central mechanisms that have been extensively described.…”
Section: Experimental Paradigmsmentioning
confidence: 87%
“…At present, data are insufficient to determine whether OID impacts the mechanisms of OIH, but studies using vancomycin to eliminate Gram-positive organisms have not observed any influence in the setting of chronic morphine exposure. 77 Regarding the opioid epidemic, the need for novel opioid-sparing strategies is self-evident. New therapeutic methods that reduce the dose and duration of opioid use are essential, as each is predictive of physical dependence, addiction, and overdose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Voltage-gated sodium channels are critical to the action potential upstroke and altered sodiumchannel kinetics in acute and chronic morphine-treated DRG and myenteric neurons have been demonstrated previously (Chen et al, 2012;Smith et al, 2012Smith et al, , 2014Mischel et al, 2018). Analysis of single-cell RNA sequencing data from Zeisel at al.…”
Section: Discussionmentioning
confidence: 99%